2013
DOI: 10.1093/jnci/djt045
|View full text |Cite
|
Sign up to set email alerts
|

Epigenome-wide Association Study of Breast Cancer Using Prospectively Collected Sister Study Samples

Abstract: Methylation profiling of blood holds promise for breast cancer detection and risk prediction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
142
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(150 citation statements)
references
References 30 publications
6
142
2
Order By: Relevance
“…Generally, cross-sectional and longitudinal analyses gave similar results, and SVA and blood cell-type correction had modest impact in reducing potential inflations of tests statistics in Q-Q plots, on occasions even resulting in overcompensation. Thus, although taking into consideration that WBC contains a mixture of cell types is important, this and other reports (27,54) have demonstrated that adjusting for blood cell subtype using current methods does not always have a substantial impact on results from EWAS. Using direct measures of blood cell composition or accounting for health conditions or medication use that could affect blood cell composition could be useful; however, these analyses were not possible in our sample.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Generally, cross-sectional and longitudinal analyses gave similar results, and SVA and blood cell-type correction had modest impact in reducing potential inflations of tests statistics in Q-Q plots, on occasions even resulting in overcompensation. Thus, although taking into consideration that WBC contains a mixture of cell types is important, this and other reports (27,54) have demonstrated that adjusting for blood cell subtype using current methods does not always have a substantial impact on results from EWAS. Using direct measures of blood cell composition or accounting for health conditions or medication use that could affect blood cell composition could be useful; however, these analyses were not possible in our sample.…”
Section: Discussionmentioning
confidence: 71%
“…Several studies have reported epigenetic traits in WBC DNA as potential cancer risk markers for solid tumors, including total genomic 5-methylcytosine (18,19) candidate genes (20)(21)(22)(23) and epigenome-wide association studies (EWAS), to identify blood-based DNA methylation signatures of risk in ovarian cancer (24), bladder cancer (25), head and neck squamous cell carcinomas (26), and breast cancer (9,27). Although EWAS report intriguing associations, replication in larger studies with prediagnostic samples is required.…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies have analyzed BC-related methylation in peripheral blood in epigenome-wide analyses, 12,20,[32][33][34] this is the first study that performed independent validation by two different techniques in large sample size. Based on several rounds of independent case-control studies on 1,500 subjects, our study demonstrated a strong association between decreased methylation of HYAL2 in peripheral blood and increased risk of BC.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19] Recently, Xu et al reported an extensive blood-based epigenome-wide association study of BC by Illumina 27K Methylation Array in a well-designed prospective sister study cohort, and demonstrated that the methylation profiling of blood are promising markers for BC detection and risk evaluation. 20 Hereby, we conducted an Infinium 27K Methylation Array on peripheral blood DNA in case-control study, and performed further independent validations by MassARRAY for BC-associated methylation variability. In addition, the association was replicated in blood cell subtypes and the correlation between gene expression and methylation was analyzed.…”
mentioning
confidence: 99%
“…In addition to multi-gene expression assays, DNA methylation signatures are being assessed as potential molecular biomarkers of cancer 8 . A number of studies have documented aberrant methylation events in breast carcinogenesis and identified specific DNA methylation biomarkers that have significant diagnostic and prognostic potential [9][10][11][12] . Several studies have also identified DNA methylation signatures that can distinguish between breast cancer subtypes [13][14][15][16] , and others that may be predictive of treatment response [17][18][19] .…”
mentioning
confidence: 99%